Jihadist terror: new threats, new responses - Richards, Anthony; Margolin, Devorah; Scremin, Nicolò (I.B. Tauris, 2019)
The past 18 months have seen a radical increase in incidents of jihadist terrorism within the United Kingdom – from the Manchester Arena attack, to the Houses of Parliament, to London Bridge. As a result, there are renewed calls for a high-level national conversation about the causes of, and the responses to, this particular terrorist problem. This book identifies policy and research gaps from an evidence-based perspective – it analyses what we know, what we don't know and what we need to know in relation to understanding and countering the jihadist terrorist threat. It provides readers with a synthesis of the knowledge and evidence that exists on each of the key topic areas, representing a distinctive and valuable resource for policymakers, academics and students. The contributors to the volume are leading international and national experts, from both the scholarly and policy-making communities, who are ideally placed to comment on the question of jihadist terrorism and the future of the threat in the UK.